Four phenylethanoids from the leaves of Pseuderanthemum carruthersii (Seem.) Guill. Var. Atropurpureum (Bull.) Fosb. - Nga, Vo Thi; Phung, Nguyen Thị Kim; Suong, Nguyen Ngoc (Vietnam Journal of Chemistry, 2012)
Four phenylethanoids were isolated from the dried leaves of Pseuderanthemum carruthersii (Seem.) Guill. var. atropurpureum (Bull.) Fosb. (Acanthaceae), including salidroside (1), darendoside B (2), verbascoside (3) and isoverbascoside (4). Their chemical structures were elucidated by spectroscopic methods. These substances were isolated for the first time from this genus.